PERILAKU KONSUMEN, KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE BRAND X - Faye Maya Dewi (Program Studi Akuntansi, 2022)
Smartphones circulate in marketing circles, making consumers more thorough in determining the smartphone they want to use. At present times, these means of communication are very important, especially in modern times. Over time progress has become rapid in the world of technology. The first purpose of this study is to optimize consumer behavior in the marketing world and product quality towards purchasing decisions in citra raya mobile stores. The survey sample contained 15 samples obtained from the questionnaire data. The study used quantitative methods and secondary data obtained directly from stores. Data tampering software analysis tool smartPLS version 3.0. The results of the assessment: (1) Consumer Behavior has no significant effect on purchasing decisions with a value of 0.754 < 1.96, (2) Product quality has no significant effect on purchasing decisions on the value of 1,348 < 1.96.